2015
DOI: 10.1016/j.jss.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of limb demand ischemia on autophagy and morphology in mice

Abstract: Background Obesity is a major risk factor for diabetes and peripheral arterial disease (PAD), which frequently leads to lower limb demand ischemia. Skeletal muscle autophagy and mitochondrial biogenesis are important processes for proper oxidative capacity and energy metabolism which are compromised in diabetes. This study compares autophagy, mitochondrial biogenesis, energy metabolism, and morphology in the hind limbs of obese diabetic mice subjected to demand or sedentary ischemia. Materials and Methods Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…This is consistent with the prior work from our laboratory showing that significant adipocyte accumulation in sedentary ischemia that was reduced by exercise [10]. UCP-1 is expressed predominantly by brown adipocytes and has been described to regulate thermogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with the prior work from our laboratory showing that significant adipocyte accumulation in sedentary ischemia that was reduced by exercise [10]. UCP-1 is expressed predominantly by brown adipocytes and has been described to regulate thermogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Adversely, demand ischemia reduced myofiber CSA (Figure 2) despite the enhanced proangiogenic response indicating substantial myofiber atrophy. However, the enhanced capillary density in our study was not expected because laser Doppler perfusion imaging in prior work from our laboratory showed that limb perfusion in demand ischemia remained diminished after one month of exercise and was not different from sedentary ischemia [10]. One possible explanation for this apparent disparity may be that the hind limb muscle which had chronic ischemia after femoral artery ligation had a distal compensatory angiogenic response in the ischemia tissue without a global increase in limb perfusion that can be detected with laser Doppler imaging.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations